2010
DOI: 10.1103/physreva.82.022102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of quantum randomness incomputability

Abstract: In contrast with software-generated randomness (called pseudo-randomness), quantum randomness can be proven incomputable; that is, it is not exactly reproducible by any algorithm. We provide experimental evidence of incomputability-an asymptotic property-of quantum randomness by performing finite tests of randomness inspired by algorithmic information theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 32 publications
2
64
0
Order By: Relevance
“…In fact, they are random less often than series of times are. Hence, we confirm the results reported in [5,6] and also our main conclusions in [1]. The reason why deviations from expected randomness occur is beyond reach, because the Innsbruck experiment was dismantled long ago.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In fact, they are random less often than series of times are. Hence, we confirm the results reported in [5,6] and also our main conclusions in [1]. The reason why deviations from expected randomness occur is beyond reach, because the Innsbruck experiment was dismantled long ago.…”
supporting
confidence: 92%
“…Although we briefly considered this issue in [1] the controversy remains, so we think pertinent to present additional data regarding the randomness of series of outcomes, to show that the conclusions reached for series of times are valid in this case too. The present contribution is not intended to be self-contained but an addendum to [1], so that paper must be at hand in what follows.Let review in few words why we had chosen to study the randomness of times instead of outcomes in the first place: i) The randomness of series of outcomes had been previously studied [5,6], and found to be surprisingly poor. In [6] (where the aim was to get a reliable source of random numbers) the cause of this drawback was identified in the blind time of the detectors, and successfully solved by using the time between coincidences (above or below the average) to generate a Borel-normal binary string.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper [13], Calude, Dinneen, Dumitrescu and Svozil have investigated very long bit sequences from four different sources: the digits of π, output from pseudo-random generators in the software packages Maple and Mathematica, and from two quantum (Quantis and a proprietary generator). They concluded that the quantum randum generators showed a statistically significant behaviour difference compared to the pseudo-random generators, but only in a subset of the tests they conducted.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not possible to strictly validate the unpredictability of such random numbers. Accordingly, if security is the highest priority, quantum random number generators (QRNGs) based on inherently unpredictable quantum processes are considered as the best choice for random number generation [5]. Plenty of physical realizations of QRNGs have been demonstrated based on effects ranging from phase fluctuations [6] and photon arrival times [7][8][9] over polarization fluctuations [10], which-way information at beams splitters [11,12] and spontaneous emission noise [13,14] up to photon number noise detection using mobile phone cameras [15].…”
Section: Introductionmentioning
confidence: 99%